Development of Digital Comics Containing Legends as a Media for Intangible Cultural Heritage for Generation Alpha - Prihantini Prihantini; Ranu Sudarmansyah; Agus Juhana; Agus Mulyana; Nurul Hidayah (STAI Hubbulwathan Duri, 2025)
This research aims to develop a digital comic that raises the legend of 'Curug Awang' as an intangible cultural heritage medium for the Alpha generation. The alpha generation is the target user of research products because they are very visual tech-savvy, and familiar with smartphones and digital media. The research method applies the Multimedia Development Life Cycle (MDLC) model. The respondents consisted of two media experts, two linguists, 31 Alpha generations, and 27 teachers. Product testing showed that digital comics met the validation criteria, achieving an average score of 3.55 from media experts and 3.45 from linguists. At the user acceptance testing stage, Generation Alpha rated it at 83.46%, while teachers rated it at 84.6%. These results show that digital comic products are a valuable educational medium. Qualitative data revealed that these comics positively influenced the Alpha generation's understanding of the important values in the legend, namely perseverance and strong determination needed in the pursuit of knowledge, as well as the importance of environmental conservation. Teachers recognize the potential of digital comics to enrich the learning experience and convey meaningful moral messages to the younger generation. The results of this research not only succeeded in documenting and revitalizing the legend of Curug Awang but also contributed to the preservation of intangible culture, as well as overcoming the gap that has not been widely developed digital comics as a transformation medium to increase the awareness of the younger generation about local cultural heritage through interesting and easily accessible media.